Wear of Biopolymers under Reciprocating Sliding Conditions against Different Counterfaces - Harsha A.P.; Wäsche R.; Joyce T.J. (My University, 2025)
The objective of this study was to investigate the wear resistance of ultrahigh-molecular weight polyethylene (UHMWPE) and crosslinked polyethylene (XLPE) against different counterfaces. Friction and wear studies were evaluated under dry reciprocating sliding conditions at room temperature. Ti6Al4V discs finished in polished, lapped, and ground conditions were reciprocated against polymer cylinders. In addition, abrasive wear studies were conducted using different abrasive grit sizes. The friction and wear properties of the two polyethylenes were strongly affected by the different counterfaces. XLPE showed important friction and wear sensitivity with the change of surface roughness of the Ti6Al4V disc, as well as with the change in abrasive grit size. Scanning electron microscopy and energy-dispersive X-ray (EDX) analysis of the worn disc surfaces and the polymer pins indicated the wear mechanisms affecting the polyethylenes. POLYM. ENG. SCI., 59:2356–2366, 2019. © 2019 Society of Plastics Engineers. © 2019 Society of Plastics Engineers